Regulation of the acetate operon in Escherichia coli: purification and functional characterization of the IclR repressor. - Cortay, J C (1991)
Growth of Escherichia coli on acetate requires operation of the anaplerotic sequence known as the glyoxylate bypass. In this pathway three different enzymes are activated: malate synthase, isocitrate lyase and isocitrate dehydrogenase kinase/phosphatase which are encoded by genes aceB, aceA and aceK, respectively. These three genes are clustered, in that order, in the same acetate (ace) operon whose expression is under the transcriptional control of the iclR gene located downstream from aceK. We have cloned the iclR gene in the pKK233-2 vector which allows optimization of both transcription and translation initiation. The IclR repressor has been overproduced, then purified to homogeneity in a one-step procedure by cation exchange chromatography after ammonium sulfate fractionation. Its specific interaction with the operator/promoter region of the ace operon has been analyzed by gel retardation and DNase I footprinting experiments. The IclR repressor has been shown to recognize a 35 bp palindromic sequence which largely overlaps the -35 recognition site of RNA polymerase. Moreover, the formation of the complex between IclR and the operator/promoter region has been found to be impaired by phosphoenol pyruvate but insensitive to acetate, acetyl-CoA, pyruvate, and oxaloacetate. These results are discussed in terms of primary regulation of the expression of the ace operon.